The molecular mechanism of lipid uptake by membrane-anchored bridge-like lipid transfer proteins - Daniel Álvarez; Paige Chandran Blair; Cristian Rocha-Roa; Michael Davey; Elizabeth Conibear; Stefano Vanni (Proceedings of the National Academy of Sciences, 2026)
Lipid transport by bridge-like lipid transfer proteins (BLTPs) is emerging as a key process in lipid and cellular metabolism in both physiological and pathological conditions. However, the precise mechanism of lipid transport by BLTPs has remained elusive. Here, we use extensive all-atom molecular dynamics simulations to characterize the precise mechanism of lipid transfer into the BLTP hydrophobic cavity from donor membranes. For multiple BLTPs, we observe the ability to extract and solubilize lipids without lipid selectivity, and we identify membrane destabilization as a critical parameter to achieve effective lipid desorption. We rationally design a mutant BLTP with altered ability to destabilize lipid bilayers, and we show that this abolishes lipid desorption in silico and protein function in vivo. Taken together, our data provide an atomic-level description of the mechanism of lipid transport by BLTPs, ultimately suggesting alternative strategies to interfere with their activity.